Revolution and constitutionalism in the Ottoman Empire and Iran - Sohrabi, Nader, 1961- (Cambridge [U.K.] : Cambridge University Press, 2011)
'In his book on two constitutional revolutions in the Middle East in the early twentieth century, Nader Sohrabi considers global diffusion of institutions and ideas, their regional and local reworking, and the long-term consequences of adaptations. He delves into historic reasons for greater resilience of democratic institutions in Turkey as compared to Iran. Arguing that revolutions are time-bound phenomena whose forms follow global models in vogue at particular historical junctures, he challenges the ahistoric and purely local understanding of them. Furthermore, he argues that macro-structural preconditions alone cannot explain the occurrence of revolutions, but global waves, contingent events, and intervention of agency work together to bring them about in competition with other possible outcomes. To establish these points, the book draws on a wide array of archival and primary sources that afford a minute look at revolutions, unfolding; these are examined against the backdrop of the differing institutional settings and middle classes in the Ottoman Empire and Iran and their similarly financially strapped states that faced strong geo-political challenges'--Provided by publisher.
Includes bibliographical references (p. 437-441) and index.
Keywords: Constitutional history -- Turkey; Constitutional history -- Iran; Revolutions -- Turkey -- History -- 20th century; Revolutions -- Iran -- History -- 20th century; Comparative government; Turkey -- Politics and government -- 1878-1909.; Turkey -- Politics and government -- 1909-1918.; Iran -- Politics and government -- 1905-1911.